HYBRID LEARNING AS AN ALTERNATIVE TO MODERN LEARNING MODELS - Insan Kamil; Riantino Yudistira; M. Yusuf; Muta’allim Muta’allim; Hasan Sayfullah (International Conference on Humanity Education and Society (ICHES), 2023)
The implementation of conventional learning models is admittedly still inseparablefrom the implementation of learning, because thislearning model isthe easiest learning modelfor teachers to do. However, currently teachers are required to be more creative andinnovative in collaborating conventional learning models with other learning models, forexample collaborating with online-based learning models or electronic learning (e-learning).The presentation of this web-based e-learning can be more interactive in learning. Thiselearning system does not have access restrictions, teaching and learning activities can becarried out in more time. The potential of this time opportunity provides an opportunity forstudents to choose their own study time, so that students have sufficient time to develop theirthinking and creativity in facing future global challenges. Hybrid Learning or BlendedLearning refersto the combination of e-learning based learning methods (electronic learning)with face-to-face learning methods or conventional methods.